The Relationship Between the Meaning of Life and Prosocial Behavior in Early Adulthood in Makassar City - Zhafirah Firna, Sitti Meydhita; Mansyur, Ahmad Yasser; Kusuma, Perdana (Polteknik Ilmu Pemasyarakatan, 2025)
Humans can increase prosocial behavior through the meaning of life. This is caused by the desire for a meaningful life within the individual. Prosocial behavior is an act of providing benefits and advantages voluntarily so that the physical and psychological needs of other individuals are met. However, individuals often do not carry out prosocial behavior because they do not have confidence in themselves. This research aims to determine the relationship between the meaning of life and prosocial behavior in early adulthood in Makassar City. This research used quantitative methods with research respondents totaling 355 early adults in Makassar City aged 18 to 25 years. The measuring instruments used in this research are the meaningfulness of life scale with a reliability value of 0.972 and the prosocial behavior scale with a reliability value of 0.911. Hypothesis testing used the Pearson correlation parametric analysis technique using the Jamovi application version 2.3.21 with results r = 0.105 and p = 0.000. The results of the research show that there is a positive relationship between the meaning of life and prosocial behavior in early adulthood in Makassar City. This means that the higher the level of meaningfulness of life, the higher the level of prosocial behavior in early adulthood. The lower the level of meaningfulness of life, the lower the level of prosocial behavior in early adulthood. The implication of this research is that it is a reference source that can contribute to knowledge regarding the meaning of life and prosocial behavior.